The backstage of democracy: exploring the professionalisation of politics in India - Sharma, AD (2020)
Many commentators have noted that since the 2014 Indian general elections, India has witnessed a new style of election campaigning that marks a decisive break from the past. Driving this change are a series of actors such as political consultants, ‘spindoctors’, campaign strategists, and specialised party staffers who have become an integral part of election campaigns and the routine affairs of party politics. In this thesis, I label such actors as ‘political professionals’ and analyse the changes ushered by them as a process of ‘professionalisation of politics’. Although the professionalisation of politics has been noted in different countries around the world, this phenomenon has not received any academic attention in the context of a developing country. Based on a 12-month period of fieldwork in New Delhi, this thesis provides an empirically grounded examination of the manifestations, causal explanations, and implications of the professionalisation of politics in India.